Acoustic communication in plant–animal interactions. (August 2016) - Schöner, Michael G; Simon, Ralph; Schöner, Caroline R
Graphical abstract: Highlights: Knowledge about sound production in plants for communication is still limited. Plants reflect animal sounds to communicate with them. Convergent echo reflectors in several plant species attract mutualistic bats. Reflectors serve as beacons, identification signals or guiding posts. Abstract : Acoustic communication is widespread and well-studied in animals but has been neglected in other organisms such as plants. However, there is growing evidence for acoustic communication in plant–animal interactions. While knowledge about active acoustic signalling in plants (i.e. active sound production) is still in its infancy, research on passive acoustic signalling (i.e. reflection of animal sounds) revealed that bat-dependent plants have adapted to the bats' echolocation systems by providing acoustic reflectors to attract their animal partners. Understanding the proximate mechanisms and ultimate causes of acoustic communication will shed light on an underestimated dimension of information transfer between plants and animals.